REFLEKSI SISTEM DISTRIBUSI SYARIAH DALAM UPAYA OPTIMALISASI PENYALURAN DANA ZAKAT DI INDONESIA - Amarudin, Muchamat (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2018)
Abstract There is a lot of literature that tries to look at zakat from various sides, such as from legal aspects (fiqh), management, potential and its role in poverty alleviation. This proves that zakat has a significant place in the realm of Islamic sciences and other sciences. The obligation of zakat in Islam has a very deep meaning. In addition to dealing with aspects of Godliness, as well as economics and social Two dimensions possessed by zakat or identites that will provide a very good impact on society, both as an effort to worship Him and as an effort to care for social with fellow human beings . However, zakat is not limited to that. Optimizing the distribution of zakat funds in a professional manner will have a better impact in efforts to distribute wealth or income to the community. Optimizing the distribution of zakat funds is still very limited to date, due to the limitations of professional institutions and human resources in the field of zakat. Indeed, in the concept of productive zakat distribution we find various types of distribution, but not all of them apply the distribution of productive zakat by using the concept of sharia distribution. Thus, it is expected that with the conception of productive distribution of sharia zakat funds it will not only provide welfare for muzaki but can also implement the concept of productive distribution in accordance with sharia guidance which is far from the magrib element.   Keywords: Reflection, Sharia Distribution, Optimization of Zakat.